1976
DOI: 10.1128/aac.9.5.780
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Selected Beta-Lactam and Aminoglycoside Antibiotics Against Cephalothin-Resistant Enterobacteriaceae

Abstract: The in vitro antibacterial activity of four 18-lactam antibiotics (cefatrizine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
9
0

Year Published

1976
1976
1982
1982

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The high degree of in vitro activity of amikacin against gentamicin-resistant Enterobacteriaceae and P. aeruginosa agrees with our previous findings reported in a smaller number of different clinical isolates (8,12). Although gentamicin and tobramycin are active against some strains ofProvidencia (7), our experience agrees with that of Overturf et al, who found gentamicin-resistant strains that were susceptible to amikacin (14).…”
supporting
confidence: 82%
See 3 more Smart Citations
“…The high degree of in vitro activity of amikacin against gentamicin-resistant Enterobacteriaceae and P. aeruginosa agrees with our previous findings reported in a smaller number of different clinical isolates (8,12). Although gentamicin and tobramycin are active against some strains ofProvidencia (7), our experience agrees with that of Overturf et al, who found gentamicin-resistant strains that were susceptible to amikacin (14).…”
supporting
confidence: 82%
“…Resistance to gentamicin among the Enterobacteriaceae and Pseudomonas aeruginosa appears to be a problem of increasing importance (5,12). At the Wadsworth VA Hospital amikacin was shown to be the most effective aminoglycoside in vitro against gentamicin-resistant Enterobacteriaceae and P. aeruginosa (8,12). Likewise, it has been highly effective in treating infections caused by gentamicin-resistant, gram-negative bacilli (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, recently a number of new cephalosporins have been synthesized that seem to have a markedly broader spectrum against gram-negative bacilli. Among the most promising are cefamandole (2,4,5,7,10), cefuroxime (5,11,12), cefatrizine (6,7,13,15), cefoxitin (3, 7-9, 11, 14), and cefazaflur (SKF 59962) (1).…”
mentioning
confidence: 99%